1. Löse die Gleichungen 
a) $x - 6 = 3$ b) $x - 6 = 3$
b) $x + 8 = 12$ c) $-x - 6 = 3$
c) $x - 12 = 18$ d) $6 - x = 1$
d) $x + 10 = 8$ f) $7 - x = 3$
e) $1 - x = 1$ i) $-x + 15 = 2$
f) $-x - 13 = -3$ p) $-x - 14 = -3$
g) $-x - 6 = -1$ q) $x - 11 = 4 + 2x$
2.Löse die Gleichungen  
a) $-3 - 2x = -3$  b) $x - 11 = -2 + 2x$
c) $3x = -54 + 7x$  d) $15 - x = x - 1$
e) $-3x = -2x - 11$  f) $-x + 20 = x + 1$
g) $-4x - 8 = 2 - 3x$  h) $-4x + 27 = -2 - 2x$
i) $9 - 5x = 2 - 4x$  j) $-11 - 4x = -1 - 3x$
k) $-5x + 13 = -4 - x$  l) $3x - 5 = -4 + 4x$
m) $2x + 1 = -3 + 3x$ n) $-3x + 18 = -x - 1$

 

3.Löse die Gleichungen
a) $-3(10 + x) + x = -4$
b) $-6(x - 3) + 4x = -4$
c) $-7(x - 5) + 3x = 3$
d) $3(7 - 2x) + 4x = -5$
e) $2x - 5(-1 - 4x) - 5 = 23x + 13$
f) $-2(4 + 3x) + 4x - 23 = -1 - 2x$
g) $-3x + 3(2 + x) = x + 6$
h) $-3(x - 13) - x = 3$
i) $4x - 5(2 + x) = 1$
j) $-3(x - 7) + x = 1$
k) $3x + 37 = 4 + (19 - 3x) + 7x$

 

4.Löse die Gleichungen
a) $81 + 3x - (41 - 3x) = 4x + 3(2 + 2x) - 1$
b) $3(1 + 3x) + 4x - (13 + 15x) + 1 = 2 - x$
c) $ x - 5(1 + 2x) = 2x - 4 + (1 - 10x)$
d) $4 - x = (3x + 1) + 3 - 3x$
e) $3x + 37 = 4 + (19 - 3x) + 7x$
f) $ -1 - (8x - 5) + 5x = -x - 5$
g) $-x + 3(-2x + 3) + 2(4 + 3x) = 4$
h) $ 71 - (37 + 6x) + 3x = 1 - 4(-2x - 2) - 11x$
i) $-3(2x - 3) = 2(7 - 3x) - 5$
j) $-(-3x + 3) - 3(-1 + x) - x = -8$
k) $2x - 4(-x + 1) - 2(2 + 3x) = -4$